Group B streptococcus infection in a sudden unexpected death of infancy – the importance of microbiological investigation at post-mortem - N., Khalid; Khairul Anuar, Zainun; Hisham, Salina; N. I., Mazan; Amin Nordin, Syafinaz (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Group B streptococcus (GBS) is a common cause of infection in newborns and in early infants. However, GBS infection in an infant older than three months is infrequently reported in the literature. We reported a case of an apparently well six-month-old infant who died of sudden death due to GBS pneumonia, diagnosed at autopsy. The six-month-old, apparently well male infant was brought in dead to the Emergency Department. He underwent medicolegal autopsy four hours after death, as part of an overall sudden unexpected death in infancy investigation (SUDI). Apart from whitish froth oozing out of both nostrils, he appeared to be well-nourished infant without any deformity, syndromic features or obvious suspicious marks of injury externally. Internal examination showed generalized hyperinflated with patchy consolidation of upper and middle lobes of bilateral lung. Multiple matted mesenteric lymphadenopathy were also detected. Blood and lung tissue specimens collected under aseptic technique yielded growth of GBS. Post-mortem histology from consolidated lungs confirmed pneumonic features while mesenteric lymph nodes showed reactive changes in-keeping with underlying infective process. Death was attributed to GBS pneumonia. This case highlights the importance of a detailed autopsy in sudden unexpected death in infancy (SUDI) and the crucial role of post-mortem microbiological study in such cases. Relevant autopsy protocols that need to be employed during microbiological sampling are briefly discussed.